EFEKTIVITAS PERENDAMAN LARUTAN EKSTRAK DAUN BABADOTAN (Ageratum conyzoides L) DENGAN KOSENTRASI BERBEDA PADA KUALITAS TELUR AYAM RAS DALAM SUHU RUANGAN - bagus uda palgunadi; Indra Rahmawati; Junianto Wika Adi Pratama; Mohammad Safrizal Alam Hudi (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2019)
In order to investigate the effect of immersion babadotan leaf extract solution (Ageratum conyzoides L) with various centration of the quality of chicken eggs in room temperature. Reviewed from the yolk index and haugh unit. The sample are 1 day chicken eggs race with an average weight of 50-60 grams, which is taken from PT. Mulya Broiler Farm, Binangun village, Binangun subdistrict, Blitar regency. It used as much as 100 eggs, with immersion treatment using Babadotan leaf extract solution for 1 minute with the centralization of the solution 30%, 40%, 50% and 60%, and stored in room temperature, than calculated the value of yolk index and haugh unit. Results of the study showed that immersion by using Babadotan leaf extract solution had no noticeable effect (P > 0.05) against the Haugh and very noticeable effect (P < 0.05) on the value of yolk Index. Quality of chicken eggs are given the immersion babadotan leaf extract solution is better than without immersion.